Interpretasi Tauhid dalam Surah Al-Ikhlas dan Perannya sebagai Kerangka Nilai Utama dalam Mewujudkan Kesetaraan Gender - Himmah Aliyah; Intihaul Fudola; Habil Abyad; Faisal Mahmoud Adam Ibrahim (SUHUF, 2025)
Gender discrimination in many Muslim societies is often sustained by patriarchal cultural norms and textualist interpretations of the Qur'an that overlook its broader ethical and egalitarian principles. This study explores how the concept of tauhid in surah Al-Ikhlas can function as both a theological and ethical foundation to challenge patriarchal structures and advance gender justice. Employing a qualitative methodology grounded in literature-based analysis, the research adopts the Living Qur’an framework in conjunction with Amina Wadud’s gender hermeneutics. Primary and secondary sources—including classical exegetical works such as those of Ibn Kasir, contemporary commentaries by scholars like Quraish Shihab and Wadud, as well as scholarly literature on gender equity—inform the analysis. The findings indicate that tauhid, beyond affirming the oneness of God, embodies anti-hierarchical and egalitarian values that reject all forms of human domination, including male supremacy. Through contextual and sociological interpretation, surah Al-Ikhlas reveals tauhid as a moral imperative to promote just and equal gender relations. This study contributes to contemporary Qur’anic scholarship by proposing a gender-responsive theological reading rooted in the lived realities and ethical aspirations of Muslim communities.